Crisis Management in the Eastern Mediterranean (Implications for Policymakers) - Loizides, Neophytos G. (Études helléniques / Hellenic Studies, 2004)
This article examines Greek-Turkish crisis behaviour in the Eastern Mediterranean over the past two decades. Crises are first defined and classified, after which a number of common misperceptions are then addressed in light of recent experience. Three broad caregories of foreign policy crises are analyzed: 1) those involving ethnically related minorities across the border, those with 'alien' minorities within borders; 2) chose with third countries involving territories and resources. The article examines whether crises are simply élire-driven or partly endorsed and motivaced by mass publics in both countries, and whecher Greek-Turkish crisis behaviour reflects enduring ethnic rivalries, 'genuine' security interests, or domestic political needs and norms. The article draws upon the Greek-Turkish experience of the past two decades to illuminate contemporary dilemmas and issues which policymakers face in this region.